The Cenozoic Vertebrate Fossils from the Nepal Himalaya: A Review - Paudayal, Khum Narayan (Journal of Natural History Museum, 2015)
The last four decades have been fruitful for recording the Cenozoic vertebrate fossils in the Nepal Himalaya. This information is very important to understand the evolution of vertebrate fauna as well as the climate in which they were living during and after the collision of the Indian subcontinent to Eurasian continent. This paper gives a review of the landmark contribution which has been made by different authors on this aspect. J. Nat. Hist. Mus. Vol. 27, 2013: 120-131